Mapas cadastrais que devem compor o planejamento do uso de terra - Ladwig, Nilzo Ivo; Costa, Suely de Souza (Geografia Ensino & Pesquisa, 2016)
Mapas cadastrais que devem compor o planejamento do uso de terra